Parents' knowledge and attitude to self-medication of children with antibiotics - Suleiman Ibrahim Sharif; Bara'ah E. M. Masalmeh; Hoda M. A. Awad; Ala Osama; Yousra A. A. Abdulmqasood; Laila M. T. Bugaighis (Archives of Global Professionals, 2015)
Objective: The aim of this study was to determine the prevalence of self-medication with antibiotics in children. Materials and Methods: This study was based on a prevalidated questionnaire distributed to 205 families in the United Arab Emirates, during the period of January-October 2014, on self-medication of their children with antibiotics. Data were collected and analyzed using Microsoft Excel® and expressed in terms of both counts and percentages. Results: The response rate was 92.7% most respondents were well educated, and with university degrees and 45 (23.7%) participants were working in the medical field or attained a medical background. The majority of children were between 1 and 12 years of age, and the family's monthly income ranged from moderate to high for most of the participants. Community pharmacy was the main source (152, 80%) of antibiotics, and the main source of information was the pharmacists, followed by doctors and medication leaflets. Reasons for self-medication with antibiotics included previous experience with symptoms (100, 52.6%), and minor illness (67, 35.3%). The majority (141, 74.2%) of participants was aware of consequences of antibiotic misuse and bacterial resistance. The most commonly utilized antibiotic for self-medication was an amoxicillin - clavulanic acid combination. Antibiotics were most commonly used without prescription for respiratory symptoms including sore throat (104, 54.7%), cold/flu (85, 44.7%), and runny nose/nasal congestion (56, 29.5%). Conclusion: Antibiotics are still used for conditions which are viral in origin and parents, misconceptions about antibiotics call for organized extensive efforts to increase public awareness of the rational antibiotic use.